Human melanopsin (OPN4) gene polymorphisms: a systematic review - Lucio-Enríquez, Kevin R.; Rubio-Valles, Mariazel; Ramos-Jiménez, Arnulfo; Pérez-León, Jorge A. (Frontiers in Neuroscience, 2025)
The melanopsin (OPN4) gene is crucial in visual and non-visual processes. Certain single-nucleotide polymorphisms (SNPs) of this gene have been linked to altered light sensitivity, photoentrainment, sleep disorders, and metabolic problems, which suggests a systemic effect of light exposure. The aim of this systematic review is to explore the current literature regarding the OPN4 gene and its SNPs, along with their associations with health-related problems. The literature search was conducted in PubMed and ScienceDirect databases using the following key terms: (“Melanopsin” OR “OPN4” OR “Opsin 4”) AND (“Polymorphism” OR “SNP” OR “Variant”). The publications were from January 1998 to February 2025. We identified 763 studies, and after screening titles, abstracts, full texts, and the inclusion and exclusion criteria, nine studies were included in the review. The review was conducted by two independent reviewers following the PRISMA guidelines. Our review revealed that some SNPs of the OPN4 gene, such as P10L, I394T, and R168C, are associated with affective states, changes in chronotype, and sleep disorders: P10L variant has been associated to seasonal affective disorder (SAD), chronotype, and chronic insomnia; I394T variant has been linked to the pupillary light response (PLR) and sleep/wake timing, while R168C variant has been associated with delayed sleep-wake phase disorder (DSWPD). Currently, the remaining SNPs have no reported associations, and the existing literature does not describe any specific molecular mechanisms through which these variants could modulate or alter OPN4 function. Future research should aim to explore these identified SNPs with alternative associations related to OPN4 functions.